Probabilistic ownership cost optimisation for video content distribution. (2015) - Goudarzi, Pejman
Ownership cost modelling and optimisation for any communication service is a challenging issue. In most previous researches, only the initial expenses are considered which are inefficient. In the current work, a more accurate cost modelling has been introduced that merges both the operational and capital costs to estimate total cost of ownership. A probabilistic approach based on stochastic optimisation theory has been devised. The mentioned approach takes into account the cost perturbations associated with constructing components of hierarchical video content delivery systems with unknown management costs. It is tried to validate the sensitivity, scalability and efficacy of the proposed method through parametric analysis and extensive simulations for different network topologies. The numerical results show the properties of the proposed model and compare it with other heuristics (such as nature-inspired gravitational search algorithm) and also the traditional methods.